Photosynthesis and net primary productivity in three Antarctic diatoms: Possible significance for their distribution in the Antarctic marine ecosystem - Petrou, K; Ralph, PJ (2011)
Photosynthesis and net primary productivity were measured in 3 Antarctic diatoms, Fragilariopsis cylindrus, Pseudo-nitzschia subcurvata and Chaetoceros sp., exposed to rapid changes in temperature and salinity representing a range of conditions found during a seasonal cycle. Measured differences in fluorescence-derived photosynthetic activity and oxygen evolution suggested that some alternative electron cycling activity was present under high irradiances. F. cylindrus displayed the highest rates of relative electron transport and net primary productivity under all salinity and temperature combinations and showed adaptive traits towards the sea-icelike environment. P. subcurvata displayed a preference for low saline conditions where production rates were greatest. However, there was evidence of photosynthetic sensitivity to the lowest temperatures and highest salinities, suggesting a lack of adaptation for dealing with sea-ice-like conditions. Chaetoceros sp. showed high plasticity, acclimating well to all conditions but performing best under pelagic conditions. The study shows species-specific sensitivities to environmental change, highlighting photosynthetic capacity as a potentially important mechanism in ecological niche adaptation. When these data were modelled over different seasons, integrated daily net primary production was greatest under summer pelagic conditions. The findings from this study support the general observations of light control and seasonal development of net primary productivity and species succession in the Antarctic marine ecosystem. © Inter-Research 2011.